Translating Marine Animal Tracking Data into Conservation Policy and Management. (May 2019) - Hays, Graeme C.; Bailey, Helen; Bograd, Steven J.; Bowen, W. Don; Campagna, Claudio; Carmichael, Ruth H.; Casale, Paolo; Chiaradia, Andre; Costa, Daniel P.; Cuevas, Eduardo; Nico de Bruyn, P.J.; Dias, Maria P.; et al.
Abstract : There have been efforts around the globe to track individuals of many marine species and assess their movements and distribution, with the putative goal of supporting their conservation and management. Determining whether, and how, tracking data have been successfully applied to address real-world conservation issues is, however, difficult. Here, we compile a broad range of case studies from diverse marine taxa to show how tracking data have helped inform conservation policy and management, including reductions in fisheries bycatch and vessel strikes, and the design and administration of marine protected areas and important habitats. Using these examples, we highlight pathways through which the past and future investment in collecting animal tracking data might be better used to achieve tangible conservation benefits. Highlights: The value of animal tracking data to inform policy is illustrated by case studies from around the world and with a broad range of taxa. Application of tracking data to policy and management can take various pathways, and engagement with stakeholders might often not be made by the original data collectors. The impact of tracking data on policy and management can be improved if data collection and analyses target specific needs for management outcomes. Early engagement among the data collectors and the stakeholders involved in policy development and implementation is important to help translate tracking data into conservation outcomes.